2021
DOI: 10.3390/ijms22031403
|View full text |Cite
|
Sign up to set email alerts
|

IGF-1 Upregulates Biglycan and Decorin by Increasing Translation and Reducing ADAMTS5 Expression

Abstract: Proteoglycan (PG) is a glycosaminoglycan (GAG)-conjugated protein essential for maintaining tissue strength and elasticity. The most abundant skin PGs, biglycan and decorin, have been reported to decrease as skin ages. Insulin-like growth factor-1 (IGF-1) is important in various physiological functions such as cell survival, growth, and apoptosis. It is well known that the serum level of IGF-1 decreases with age. Therefore, we investigated whether and how IGF-1 affects biglycan and decorin. When primary cultur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 64 publications
(82 reference statements)
0
4
0
Order By: Relevance
“…Total RNA was isolated from cultured HaCaT cells using RNAiso Plus (Takara Bio Inc., Shiga, Japan) at 18 h after TNF-α/IFN-γ-stimulation. Subsequent cDNA synthesis and product confirmation by real-time PCR was performed as detailed in our previous report [ 66 ]. The following primer sequences were used for amplification: TARC forward: 5′-TTGTAACTGTGCAGGGCAGG-3′, reverse: 5′-TGAACACCAACGGTGGAGGT-3′, MDC forward: 5′-GAAGCCTGTGCCAACTCTCT-3′, reverse: 5′-GGGAATCGCTGATGGGAACA-3′, CTSS forward: 5′-TGGGCTTTCAGTGCTGTGGG-3′, reverse: 5′-TCAATGATGTACTGGAAAGC-3′, 18S rRNA forward: 5′-GTAACCCGTTGAACCCCATT-3′, reverse: 5′-CCATCCAATCGGTAGTAGCG-3′, GAPDH forward: 5′-ATTGTTGCCATCAATGACCC-3′, reverse: 5′-AGTAGAGGCAGGGATGATGT-3′, U6 snRNA forward: 5′-CTCGCTTCGGCAGCACA-3′, and reverse: 5′-AACGCTTCACGAATTTGCGT-3′.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Total RNA was isolated from cultured HaCaT cells using RNAiso Plus (Takara Bio Inc., Shiga, Japan) at 18 h after TNF-α/IFN-γ-stimulation. Subsequent cDNA synthesis and product confirmation by real-time PCR was performed as detailed in our previous report [ 66 ]. The following primer sequences were used for amplification: TARC forward: 5′-TTGTAACTGTGCAGGGCAGG-3′, reverse: 5′-TGAACACCAACGGTGGAGGT-3′, MDC forward: 5′-GAAGCCTGTGCCAACTCTCT-3′, reverse: 5′-GGGAATCGCTGATGGGAACA-3′, CTSS forward: 5′-TGGGCTTTCAGTGCTGTGGG-3′, reverse: 5′-TCAATGATGTACTGGAAAGC-3′, 18S rRNA forward: 5′-GTAACCCGTTGAACCCCATT-3′, reverse: 5′-CCATCCAATCGGTAGTAGCG-3′, GAPDH forward: 5′-ATTGTTGCCATCAATGACCC-3′, reverse: 5′-AGTAGAGGCAGGGATGATGT-3′, U6 snRNA forward: 5′-CTCGCTTCGGCAGCACA-3′, and reverse: 5′-AACGCTTCACGAATTTGCGT-3′.…”
Section: Methodsmentioning
confidence: 99%
“…To extract the proteins for western blotting, cells were harvested by scraping on ice with 1× SDS-lysis buffer containing high concentrations of SDS (1.75%) and 2-mercaptoethanol (715 mM), along with the Complete Mini protease inhibitor cocktail (Roche Applied Science, Indianapolis, IN, USA) and phosphatase inhibitor cocktails (Sigma-Aldrich, St. Louis, MO, USA). Subsequent processes were performed as detailed in ourprevious report [ 66 ]. Membranes were blocked using 5% BSA in tris-buffered saline with 0.1% Tween ® 20 (TBS-T), instead of 5% skim milk in TBS-T for the phospho-forms of target proteins.…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, recent studies have revealed that IGF-1 increases biglycan protein translation by preventing ADAMTS5-mediated degradation indicating a new role of IGF-1 regulating biglycan expression [214]. Since biglycan activates fibroblasts, inducing tumor stiffness [215] and facilitating tumor cell invasion, its interactions with IGF-signaling could present a plausible cancer therapy target.…”
Section: Igf Signaling In Tumor Angiogenesismentioning
confidence: 99%
“…Under normal circumstances the expression and activity of proteases in skin and other organs is tightly regulated to prevent excessive tissue destruction which could lead to chronic disease and loss of tissue function [6]. In healthy skin, the mechanisms that mediate protease activity occur at multiple levels, from the control of protease gene transcription [7] through to secretion of proteases as inactive zymogens [8], and the selective activation [9] and suppression of activity by specific inhibitors [10]. However, failure of these mechanisms, through genetic or acquired causes, may contribute to excessive protease activity and the development of skin conditions such as Netherton syndrome [11], rosacea [12], chronic wounds [13] and photoageing [14].…”
Section: Introductionmentioning
confidence: 99%